2014
DOI: 10.1210/jc.2013-2647
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Improve Muscle Strength in Adults? A Randomized, Double-blind, Placebo-controlled Trial Among Ethnic Minorities in Norway

Abstract: Daily supplementation with 25 or 10 μg vitamin D3 for 16 weeks did not improve muscle strength or power measured by the jump test, handgrip test, or chair-rising test in this population with low baseline vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 44 publications
4
52
2
Order By: Relevance
“…In the current study, very few of our participants had 25(OH)D concentrations greater than 50 nmol/L and yet an association between 25(OH)D and muscle strength was observed. In a previous RCT among immigrants in Oslo, it was also reported that even after supplementation, 62% (in 400 IU vitamin D group) and 43% (1000 IU vitamin D group) of the participants in the study did not reach serum 25(OH)D levels ≥ 50 nmol/L [1]. It is worth pointing out that the target of 50 nmol/L is primarily based on studies performed in Caucasians and some studies suggest that the association between 25(OH)D and health outcomes are different in other ethnic groups [36].…”
Section: Factors Affecting Vitamin D Statusmentioning
confidence: 84%
See 2 more Smart Citations
“…In the current study, very few of our participants had 25(OH)D concentrations greater than 50 nmol/L and yet an association between 25(OH)D and muscle strength was observed. In a previous RCT among immigrants in Oslo, it was also reported that even after supplementation, 62% (in 400 IU vitamin D group) and 43% (1000 IU vitamin D group) of the participants in the study did not reach serum 25(OH)D levels ≥ 50 nmol/L [1]. It is worth pointing out that the target of 50 nmol/L is primarily based on studies performed in Caucasians and some studies suggest that the association between 25(OH)D and health outcomes are different in other ethnic groups [36].…”
Section: Factors Affecting Vitamin D Statusmentioning
confidence: 84%
“…Further investigation of their earlier study found that the improvement in hand grip strength was only in males, suggesting a possible gender-specific difference [34]. With lower doses of vitamin D supplementation (400 IU/day and 1000 IU/day), no significant improvement in muscle strength was seen among immigrants with ethnic backgrounds of Middle Eastern, African and South Asian in Oslo (aged 18-50 years) [1]. It is worth noting that hand grip strength was used to assess muscle strength in all of these three RCTs, which has been found to be less sensitive in assessing changes in muscle strength and physical performance [7,35].…”
Section: Factors Affecting Vitamin D Statusmentioning
confidence: 90%
See 1 more Smart Citation
“…30 In critically ill patients, interventional studies have shown vitamin D supplementation to be safe at a low IV dose 500 IU per day 55 and a single high enteral dose of 540,000 IU per day without causing significant hypercalcemia or hypercalciuria. 56 In an observational trial of 258 critically ill trauma, vascular, and surgical patients, where it was standard practice to supplement with 50,000 IU of enteral vitamin D per week, there were no reported adverse reactions or hypercalcemia.…”
Section: Safetymentioning
confidence: 99%
“…Knowledge about vitamin D and muscle function in a younger adult population is limited. Vitamin D supplementation increased muscle power in young Arabic women (16) and improved physical performance in a small trial in 40 healthy volunteers with hypovitaminosis D (17), but not all studies showed an effect (18).…”
Section: Introductionmentioning
confidence: 97%